Prospects for the Use of Private Sector Capital in the Development of High-Tech Industry - Kemenov, Alexey V.; Okatyev, Nikolay A.; Proskuri, Vladimir K.; Proskurin, Boris V. (Journal of Reviews on Global Economics, 2018)
Relevance: The solution to the problems of competitiveness of innovative technologies and products in global markets, accelerating the process of import substitution (if existing international economic sanctions by Russia) perhaps with the active using the capital of private business. This calls for the formation of certain financial and economic conditions of overcoming the barriers of innovative development of enterprises. The novelty of the present scientific research is in the following: the main vectors of transformation of innovative development of high-tech industrial enterprises, the necessity of wide use of capital of private business in the form of portfolio investments co-financed by the innovative projects. Practical usefulness. The increase in the share capital of private business in implementing innovative programs will reduce the financial burden on the federal budget. To increase the possibility of accelerating the processes of development of public-private partnerships and venture financing. Will expand the scope of use of the capital of private business in creating science-based dual-use products, implementation-oriented private commercial contracts in various sectors of the economy. Â The future economic development of the country depends on the development and implementation of new technological researches that can make a certain breakthrough in providing technological and economic growth. The life cycle (LC) of any innovation embodied in specific correlation: Innovative idea → Conducting of fundamental research studies → R&D → Pilot production → Mass production → Gradual elimination of aging equipment and technology with better analogues.